2019
DOI: 10.5539/ass.v15n2p37
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Demographic Dividend Nexus in Nigeria: A Vector Autoregressive (VAR) Approach

Abstract: In demography and population economics discourse, the macroeconomic implications of an upsurge in working age population, notably the labour force, on economic growth has been widely studied and the inherent beneficial impact has become known as demographic dividend. However, the exact mechanism linking the dividend to growth remains a perennial question. This motivates the current study to investigate empirically the dividend-growth nexus in the context of Nigerian economy in a multivariate VAR model spanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Nigeria is the fastest growing country in sub-Saharan Africa (SSA) in terms of the human population (Akombi et al 2019;Young 2019). Improved water supply which is one of the essentials for a healthy living has been constrained by uncontrolled anthropogenic activities (Vijay et al 2011;Qin et al 2013;Chen et al 2016;Chitsazan et al 2019) and by lesser extent natural conditions (Izah et al 2016;Makinde et al 2017;Zadawa and Omran 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria is the fastest growing country in sub-Saharan Africa (SSA) in terms of the human population (Akombi et al 2019;Young 2019). Improved water supply which is one of the essentials for a healthy living has been constrained by uncontrolled anthropogenic activities (Vijay et al 2011;Qin et al 2013;Chen et al 2016;Chitsazan et al 2019) and by lesser extent natural conditions (Izah et al 2016;Makinde et al 2017;Zadawa and Omran 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the study revealed that both variables had a long-run relationship; moreover, uni-directional causality between population and economic growth running from former to the later was found. Ademola (2019) investigated the nexus between demographic dividend and economic growth in the Nigerian economy. By using time series data spanning from the year 1970 to 2017, and multivariate VAR model, their study showed that, the innovation in gross enrolment contributed to economic growth relative to innovation in economic support ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Ademola (2019), econometric literature proposes, contingent on time-series features of variables, three distinct methodological alternates to empirically analyze the dynamic interactions between time series variables. These are, a VAR Model with the level, I(0) data, a VAR model with first-differenced, I(1) data, and a vector error correction model (Hundie, 2014).…”
Section: Toda -Yamamoto Approach For Causality Analysismentioning
confidence: 99%